2003
DOI: 10.1161/01.cir.0000101684.88679.ab
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study Comparing Combined Pulmonary Vein–Left Atrial Junction Disconnection and Cavotricuspid Isthmus Ablation Versus Pulmonary Vein–Left Atrial Junction Disconnection Alone in Patients Presenting With Typical Atrial Flutter and Atrial Fibrillation

Abstract: Background— Atrial flutter (AFL) and atrial fibrillation (AF) frequently coexist in the same patient. Recently it has been demonstrated that the triggers for both AF and AFL may originate in the pulmonary veins (PVs). We hypothesized that in patients with both AF and typical AFL, pulmonary vein–left atrial junction (PV-LAJ) disconnection may eliminate both arrhythmias. Methods and Results— Consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 34 publications
9
119
0
2
Order By: Relevance
“…Between the 3 ablation approaches for coexistent AF and AFL, several studies have demonstrated that the combined ablation strategy (PVAI+CTI) results in very low AF recurrence, 14,15 that PVAI alone without CTI ablation has an early recurrence of AFL in 24%, 16 and that the rate of AF recurrence after CTI isolation alone has been reported to be as high as 80% and up to 30% in those on AADs after isthmus isolation. 16 Roithinger et al 17 hypothesized that AF organizes to AFL in patients presenting with both arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Between the 3 ablation approaches for coexistent AF and AFL, several studies have demonstrated that the combined ablation strategy (PVAI+CTI) results in very low AF recurrence, 14,15 that PVAI alone without CTI ablation has an early recurrence of AFL in 24%, 16 and that the rate of AF recurrence after CTI isolation alone has been reported to be as high as 80% and up to 30% in those on AADs after isthmus isolation. 16 Roithinger et al 17 hypothesized that AF organizes to AFL in patients presenting with both arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Bertaglia et al 17 showed clearly that the recurrence of AF after CTI block alone increases progressively over time. Wazni et al 18 randomized patients with AF and flutter in two groups, one of them only for PV isolation and the other for isolation plus CTI block, and observed, in a follow-up shorter than one year, that isolation alone was able to control both arrhythmias, although isthmus block could prevent the early recurrence of arrhythmias. In the present study, however, the association of isolation and CTI block reduced recurrences also in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The most common location is the roof between the right additional lines or PV isolation with complex fractionated electric potential ablation. 66 Even in unique subsets of AF population such as coexistent AF and typical atrial flutter 67,68 and AF and perimitral flutter, 69 isthmus lines were found to have limited impact on arrhythmia recurrence. Therefore, the benefits of linear lesions as an adjunctive therapy remain unclear.…”
Section: 53-55mentioning
confidence: 99%